Asymptotic Formulae via a Korovkin-Type Result - Daniel Cárdenas-Morales; Pedro Garrancho; Ioan Raşa (Abstract and Applied Analysis)
We present a sort of Korovkin-type result that provides a tool to obtain asymptotic formulae for sequences of linear positive operators.